2020
DOI: 10.1177/0883073820966917
|View full text |Cite
|
Sign up to set email alerts
|

Seizures Are Associated With Brain Injury in Infants Undergoing Extracorporeal Membrane Oxygenation

Abstract: Objective: Determine seizure frequency and association with neurologic outcomes in infants undergoing extracorporeal membrane oxygenation. Identify patient or clinical factors associated with seizures or brain injury on imaging. Methods: Retrospective, single-center study including infants less than 1 year of age, who underwent extracorporeal membrane oxygenation between 2012 and 2017. Results: A total of 104 infants met study criteria including 45 patients with continuous electroencephalographic (EEG) monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…Electroencephalogram (EEG) is an important tool for neurological assessment. Early monitoring of EEG is necessary during ECMO, especially after ECMO initiation to 48 h after extubation, when the degree of abnormalities and the severity of the neuroimaging findings are clearly correlated and seem to predict the neurological outcome ( 40 , 41 ). Electroconvulsive features were reported to be found on the EEG of the ipsilateral side of children on ECMO with unilateral arterial cannulation, which seemed to illustrate the association of abnormal cerebral hemodynamic changes and impairments of neurological function ( 42 ).…”
Section: Evaluation Of the Nervous System After Reconstruction Or Lig...mentioning
confidence: 99%
“…Electroencephalogram (EEG) is an important tool for neurological assessment. Early monitoring of EEG is necessary during ECMO, especially after ECMO initiation to 48 h after extubation, when the degree of abnormalities and the severity of the neuroimaging findings are clearly correlated and seem to predict the neurological outcome ( 40 , 41 ). Electroconvulsive features were reported to be found on the EEG of the ipsilateral side of children on ECMO with unilateral arterial cannulation, which seemed to illustrate the association of abnormal cerebral hemodynamic changes and impairments of neurological function ( 42 ).…”
Section: Evaluation Of the Nervous System After Reconstruction Or Lig...mentioning
confidence: 99%
“…There was no significant increase in hospital stay in the EEG seizures group compared to the no EEG seizures group [weighted mean difference (WMD) = 4.2 days; 95%CI: –2.499 to 10.931; P = 0.218] ( 16 , 17 ). Meanwhile, no statistical significance was detected in the EEG seizures group after ECMO (WMD: 3.301 days; 95%CI: –20.072 to 26.673; p = 0.782) ( 6 , 18 ) in pediatric. However, a dramatic increase was observed in the group of EEG seizures after CPB as compared with the no EEG seizures group (WMD = 8.8 days; 95%CI: 1.3–16.385; P = 0.022) in pediatric ( 19 22 ).…”
Section: Resultsmentioning
confidence: 91%
“…There was significant variation among children’s hospitals in the application of EEG with increasing use observed during the study period. This increase in use may reflect increasing awareness of seizures in children supported by ECMO and practice change toward more proactive neuromonitoring [ 3 , 6 , 27 , 28 ]. There did not seem to be a connection in our data between the rate of EEG use at a hospital and the diagnosis of seizures or use of antiseizure medication.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective multicenter observational study reported an incidence of 4% and 16% for ischemic and hemorrhagic neurologic complications of children on ECMO, respectively [2]. Also, single-center studies have demonstrated seizures in 17-40% of ECMO patients, many of which were only detectable on electroencephalography (EEG) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%